2019
DOI: 10.17309/tmfv.2019.4.03
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Maximum Aerobic Speed Performance and Volleyball Game Motor Power-Explosive Abilities

Abstract: Purpose. This study aims to estimate the relevant maximum aerobic speed performance and its relationship with volleyball game motor power-explosive abilities. Shown in rugby and soccer science literature, maximal aerobic speed is considered as a critical factor for improving the athlete’s ability to recover from high-intensity and fatiguing actions.  Materials and methods. To achieve this goal, we categorised the motor abilities (vertical jump, spike approach, block jump, 20-meter sprint, T-Test (agility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The assessment of the impact of physical development parameters on the level of motor coordination in female volleyball players at the stage of specialized basic training gave reason to believe that in the process of long-term training there is a need for targeted individual correction of motor abilities development, taking into account the sensitive periods of motor abilities development (Boichuk et al, 2018(Boichuk et al, , 2021. Similar processes were recorded in experimental studies of the team of authors (Kumar et al, 2021;Zerf et al, 2019), which show that special exercises are an effective means of developing coordination abilities and contribute to the formation of specialized psychophysiological functions that ensure the effectiveness of the competitive activity in volleyball. Based on the study of special literature and the results of their own studies, researchers summarized the ways of improving the special physical training of highlyskilled volleyball players in the preparatory (Trajkovic et al, 2012) and competitive periods (Malikova et al, 2018) of the annual macrocycle and showed their role in achieving a steady effect for maximum fulfilment of female athletes' technical and tactical potential in the competitive process.…”
Section: Introductionmentioning
confidence: 82%
“…The assessment of the impact of physical development parameters on the level of motor coordination in female volleyball players at the stage of specialized basic training gave reason to believe that in the process of long-term training there is a need for targeted individual correction of motor abilities development, taking into account the sensitive periods of motor abilities development (Boichuk et al, 2018(Boichuk et al, , 2021. Similar processes were recorded in experimental studies of the team of authors (Kumar et al, 2021;Zerf et al, 2019), which show that special exercises are an effective means of developing coordination abilities and contribute to the formation of specialized psychophysiological functions that ensure the effectiveness of the competitive activity in volleyball. Based on the study of special literature and the results of their own studies, researchers summarized the ways of improving the special physical training of highlyskilled volleyball players in the preparatory (Trajkovic et al, 2012) and competitive periods (Malikova et al, 2018) of the annual macrocycle and showed their role in achieving a steady effect for maximum fulfilment of female athletes' technical and tactical potential in the competitive process.…”
Section: Introductionmentioning
confidence: 82%
“…Taking into account the leading role of the content in relation to the form, experts adhere to the position of the leading role of motor abilities. Hence it follows that the formation of skills can be successful only if this process is preceded by the process of purposeful development of motor abilities [27,28]. Therefore, the organic relationship of physical and technical training of volleyball players (girls) is considered as one of the leading principles of sports improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the literature has sufficiently fully disclosed criteria for evaluating speed-power preparedness in relation to various sports [23,26]. Nevertheless, the problem of controlling coordination abilities is not yet fully covered [9,29].…”
Section: Discussionmentioning
confidence: 99%